The Effect of Problem Solving Learning Model on Literacy and Numeracy of Grade IV Students - Baharuddin, Astuti; Alannasir, Wahyullah; Musbaing, Musbaing (ALENA : Journal of Elementary Education, 2025)
The effect of problem solving learning model on literacy and numeracy of fourth grade students of SDN 640 Ponnori, Luwu district.This study aims (1) to determine the description of the problem solving learning model in student learning in class IV SDN 640 Ponnori, (2) to determine the description of literacy and numeracy in class IV students of SDN 640 Ponnori, and (3) to determine the effect of the problem solving learning model on literacy and numeracy of students in class IV SDN 640 Ponnori. This type of research is descriptive quantitative research. The method used in this research is Quasy Experiment research . The population in this study were all grade IV students of SDN 640 Ponnori. The sampling technique used saturated sampling. The data collection techniques used were observation, tests, and documentation. The data analysis technique used is descriptive and inferential analysis. The results showed that: 1) The description of the problem solving learning model in student learning in class IV SDN 640 Ponnori is well implemented. This can be seen from the implementation of the aspects observed in the teacher observation sheet using the learning model obtained a score of 86.6% which is included in the high category. 2) The picture of literacy and numeracy of students in class IV SDN 640 Ponnori has increased. The results of the final test conducted obtained a percentage value of 88.68% which is included in the very high category.3) The problem solving learning model affects the literacy and numeracy of fourth grade students of SDN 640 Ponnori. This can be seen from the results of hypothesis testing with a significance value of 0.000 <0.05, meaning that there is an effect of using the problem solving learning model on literacy and numeracy of grade IV students of SDN 640 Ponnori.